Extenders use flexible in seed dropping in crop coffee at first harvest - Santinato, Felipe; Costa, Thaís Mello da; Silva, Rouverson Pereira da; Tavares, Tiago de Oliveira; Alcântara, Aline Spaggiari (Coffee Science - ISSN 1984-3909, 2016)
The coffee harvest of the first crop can be benefited by the use of rubber extenders at the end of the stems. This because their malleable constitution acquires oscillatory motion increasing the stem contact area with the fruits. However, the coffee varieties have big morphological and physiological differences that can influence the mechanical harvesting. This study had a goal to test two of coffee harvesters (conventional and adapted to the harvest of the first crop plantations) in the absence and presence of rubber extenders in two cultivars (Catuaí Vermelho IAC 144 and Tupi IAC 1669-33). The design was randomized blocks in five plants per plot. Evaluated the amount of fallen coffee, remaining harvested, picked and operational defoliation. Evaluated the amount of fallen coffee, remaining harvested and operational defoliation. There was obtained that the use of rubber extenders increases the amount of coffee collected in 16.6%. The first crop coffee harvest should be made with harvester adapted to this situation. The Cultivar Tupi IAC 1669-33 has high difficulty to be mechanically harvested the first crop, should be taken with two mechanized operations.